Multidisciplinary Undergraduate Research Team via Independent Study Courses. Issue 1762 (14th May 2015) - Gipson, Kyle G.
ABSTRACT: Undergraduate students from Engineering, Physics, Geology & Chemistry come together to form multidisciplinary teams as part of an undergraduate research opportunity through a sequence of independent study classes within the Department of Engineering at James Madison University. The undergraduate research groups typically contain students from freshman to senior years, totaling approximately three to eight students per academic year per group. One of the primary objectives is to provide a high-level research experience for undergraduates in a nurturing environment within the academic year. Peer-mentoring is integral piece to the team dynamics. The course sequence that facilitates the research opportunity is constructed in order for students to produce research that can be applied to obtaining a minor in Materials Science. Methodologies employed in the course range from problem-based learning, inquiry-based learning, and collaborative efforts with outside entities. The course objectives are geared towards developing critical & creative thinking, technical writing and oral communication skills through the development of planned action & experiments with data analysis as well as submitting findings to be presented at regional and national conferences.